Visualizing 3D objects from 2D cross sectional images displayed in-situ versus ex-situ - Wu, Bing (2010)
The present research investigates how mental visualization of a 3D object from 2D cross sectional images is influenced by displacing the images from the source object, as is customary in medical imaging. Three experiments were conducted to assess people’s ability to integrate spatial information over a series of cross sectional images, in order to visualize an object posed in 3D space. Participants used a hand-held tool to reveal a virtual rod as a sequence of cross-sectional images, which were displayed either directly in the space of exploration (in-situ) or displaced to a remote screen (ex-situ). They manipulated a response stylus to match the virtual rod’s pitch (vertical slant), yaw (horizontal slant), or both. Consistent with the hypothesis that spatial co-location of image and source object facilitates mental visualization, we found that although single dimensions of slant were judged accurately with both displays, judging pitch and yaw simultaneously produced differences in systematic error between in-situ and ex-situ displays. Ex-situ imaging also exhibited errors such that the magnitude of the response was approximately correct but the direction was reversed. Regression analysis indicated that the in-situ judgments were primarily based on spatio-temporal visualization, while the ex-situ judgments relied on an ad hoc, screen-based heuristic. These findings suggest that in-situ displays may be useful in clinical practice by reducing error and facilitating the ability of radiologists to visualize 3D anatomy from cross sectional images.